2015
DOI: 10.3389/fmicb.2015.00773
|View full text |Cite
|
Sign up to set email alerts
|

Hha has a defined regulatory role that is not dependent upon H-NS or StpA

Abstract: The Hha family of proteins is involved in the regulation of gene expression in enterobacteria by forming complexes with H-NS-like proteins. Whereas several amino acid residues of both proteins participate in the interaction, some of them play a key role. Residue D48 of Hha protein is essential for the interaction with H-NS, thus the D48N substitution in Hha protein abrogates H-NS/Hha interaction. Despite being a paralog of H-NS protein, StpA interacts with HhaD48N with higher affinity than with the wild type H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 84 publications
(140 reference statements)
3
9
0
Order By: Relevance
“…Although it lacks a separate DNA-binding domain (DBD) present in H-NS and StpA, Hha regulates many genes in association with H-NS (Figure 1A and B ; Refs. 17 , 20 , 21 ), and may affect others independently of H-NS ( 22 ).…”
Section: Introductionmentioning
confidence: 99%
“…Although it lacks a separate DNA-binding domain (DBD) present in H-NS and StpA, Hha regulates many genes in association with H-NS (Figure 1A and B ; Refs. 17 , 20 , 21 ), and may affect others independently of H-NS ( 22 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Hha-YdgT have been shown to favor H-NS DNA-bridging activity, thanks to conformational changes of H-NS from a close to an open state [54]. On the contrary, few reports show that Hha binds to specific regulatory sequences independently of H-NS, although Hha has no DNA binding domain [38,39,55]. A few other papers report a Hha direct regulation but careful interpretation should be done since, in these studies, Hha protein purification was performed in wild-type E. coli and thus a co-purification of Hha with H-NS and/or StpA could have occurred [56,57].…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, we cannot completely rule out the hypothesis that Hha-YdgT act indirectly through another unknown regulatory protein. A recent work identified 120 genes regulated by Hha independently of H-NS/StpA [39] among which two fimbrial genes belonging to sth and stj operons, but not the pef operon. However, bacteria were grown in neutral medium in this study and consequently not in conditions optimal for Pef expression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of plasmid R1 and R100, it has been conclusively shown that transcription initiated at the P Y promoter proceeds well beyond the finO gene and includes the rmoA (hha) gene (141). Hha is a H-NS-like nucleoid-associated protein (NAP) that can modulate gene expression in enterobacteria (142) together with or independently of H-NS (143). Like Hha, another protein, TraR, which is a RNAP modulator is encoded on the tra operon and is therefore coregulated with DNA transfer genes.…”
Section: Regulation Of Dna Transfer Genes: On and Off Switchesmentioning
confidence: 99%